Entrepreneurship in Islam (Foundations and Motivation for Entrepreneurship in Islam) - Faizatul Husna; Holilur Rahman (Al-Fadilah: Islamic Economics Journal, 2024)
Islam is the most perfect religion, a religion that regulates all aspects of life, not only from the worldly aspect but also the afterlife. In Islam worldly rules are explained and regulated through the Qur'an and Hadith. One of the perfections of Islam is that it requires its followers to be able to live independently by working or doing business in the right way. In living independently, Islam teaches us to be entrepreneurial. In writing this article, we will explain the foundation and motivation for entrepreneurship that must be applied in entrepreneurial activities. And the research method used is library research, namely research carried out by collecting data from books which are used as data sources. The concept of entrepreneurship in Islam which is given by Islam as a recommendation for entrepreneurship is implied as our basis for trying and developing ourselves, namely as stated in the Al-Qur'an and Hadith. And the thing that must be developed and applied within a person or group is motivation. With motivation, a person can be encouraged to make efforts to achieve a goal in fulfilling survival.